2020
DOI: 10.1111/aos.14548
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary management of auto‐immune ocular diseases in adult patients by ophthalmologists and rheumatologists

Abstract: Purpose Management of chronic vision threatening auto‐immune ocular diseases (AIOD, e.g. uveitis, scleritis) can be challenging. Guidelines recommend a multidisciplinary approach (MDA) with ophthalmologists and rheumatologists, to enhance the recognition of systemic diseases and guide the use of immunosuppressives. However, the indications and results of such an approach have not yet been studied. Methods A monocentre, retrospective chart review of all patients treated in a MDA between ophthalmologists and rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…[19] They reported that these forms of multidisciplinary team collaboration generates favorable clinical outcomes: supporting the usage of IMT, tapering corticosteroid dosage, and leading to new diagnoses of underlying systemic diseases. [19] The clinical approach described is different from our combined clinic. Practically, it may be di cult to have frequent multidisciplinary meetings for uveitis, but a combined clinic may be more feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] They reported that these forms of multidisciplinary team collaboration generates favorable clinical outcomes: supporting the usage of IMT, tapering corticosteroid dosage, and leading to new diagnoses of underlying systemic diseases. [19] The clinical approach described is different from our combined clinic. Practically, it may be di cult to have frequent multidisciplinary meetings for uveitis, but a combined clinic may be more feasible.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] The need for long-term therapy for chronic uveitis and possible associated systemic autoimmune diseases, therefore, necessitates the prescription of immunomodulatory agents which requires co-management with rheumatologists for careful monitoring of disease activities and medication side effects. [18,19,23] Previous studies have demonstrated that one of the most important reasons for ophthalmologists to consult rheumatology is the need for therapeutic advice regarding systemic IMT. [19] A recent report concerns that the majority of ophthalmologists are not familiar with the usage of IMT in managing uveitis, leading to delays in corticosteroid tapering.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in our sample we think that the way this NIU clinic is organized enhances a corticoid-sparing approach in our patients, decreasing morbidity and optimizing prognosis. 8 Active discussion of medical history and investigations, reviewing imaging exams in the team, can be an authentic game-changer when it comes to decision-making in entangled cases. 35 Not only patients but also clinicians benefit from multidisciplinary work.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Hence, there is a significant burden for the healthcare systems and the working-age population associated with NIU. 7,8 In particular, NIU is associated with late and often incorrect diagnosis, adverse outcomes, irreversible structural complications, limited clinical expertise and low-grade evidence for best practice. 3,7 Multidisciplinary teams (MDT) have been recognized in the literature as the core model for managing complex chronic conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation